2012
DOI: 10.1002/ana.23690
|View full text |Cite
|
Sign up to set email alerts
|

Central axons preparing to myelinate are highly sensitivity to ischemic injury

Abstract: Objective Developing central white matter is subject to ischemic-type injury during the period that precedes myelination. At this stage in maturation, central axons initiate a programme of radial expansion and ion channel re-distribution. Here we test the hypothesis that during radial expansion axons display heightened ischemic sensitivity, when clusters of Ca2+ channels decorate future node of Ranvier sites. Methods Functionality and morphology of central axons and glia were examined during and after a peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 62 publications
2
39
0
Order By: Relevance
“…As we previously reported [23], large (> 0.4 m in diameter) pre-myelinating axons are more sensitive to OGD than smaller premyelinated and myelinating axons. Blockade of NMDA and non-NMDA GluRs alone provides only partial protection from ischemic injury whereas addition of L-type and P/Q-type voltage-gated calcium channel (VGCC) blockers to these GluRs antagonists results in complete recovery of the compound action potential [23,37].…”
Section: Loss Of Axonal Fibressupporting
confidence: 68%
See 3 more Smart Citations
“…As we previously reported [23], large (> 0.4 m in diameter) pre-myelinating axons are more sensitive to OGD than smaller premyelinated and myelinating axons. Blockade of NMDA and non-NMDA GluRs alone provides only partial protection from ischemic injury whereas addition of L-type and P/Q-type voltage-gated calcium channel (VGCC) blockers to these GluRs antagonists results in complete recovery of the compound action potential [23,37].…”
Section: Loss Of Axonal Fibressupporting
confidence: 68%
“…Comparison of OGD-induced damage to small (< 0.4 m) and to large (>0.4 m) premyelinating axons shows that the former are protected by GluR blockers alone, whilst the latter needs addition of VGCC-blockers to confer protection [23]. This study shed light on the importance of VGCC in this age group, and on the pathophysiological mechanism of injury during ischemia in these very sensitive axons.…”
Section: Loss Of Axonal Fibresmentioning
confidence: 67%
See 2 more Smart Citations
“…Glutamate-mediated axonal injury appears related to a mechanism of excessive glutamate depletion from OLs and axons (Fern et al 1998; Fern and Moller 2000; Salter and Fern 2005; Wilke et al 2004), which appear to be the major sources of extracellular glutamate during energy failure from hypoxia-ischemia (Back et al 2007). Recently, it was shown that axons also display maturation-dependent vulnerability to oxidative stress and hypoxia-ischemia (Alix et al 2012). Larger caliber axons, which are preparing to myelinate, are particularly susceptible to injury via axolemma-associated voltage-gated calcium channels, in contrast to smaller caliber unmyelinated axons, which are more resistant.…”
Section: Cellular-molecular Mechanisms Of Acute Wmimentioning
confidence: 99%